2019
DOI: 10.3390/app9153043
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacturing, and Flight Testing of an Experimental Flying Wing UAV

Abstract: This paper presents the design, manufacturing, and flight testing of an electric-powered experimental flying wing unmanned aerial vehicle (UAV). The design process starts with defining the performance requirements including the stall speed, maximal speed, cruise altitude, absolute ceiling, and turn radius and speed. The wing loading and associated power loading are obtained based on the defined performance requirements. The wing area, UAV mass, and power requirements are determined from the endurance and paylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…To obtain maximum power output which the propeller delivers, efficiencies must be taken into account as given in Eq. 1 [18].…”
Section: Power and Mass Estimation Of Unmanned Aircraft System-based Pem Fuel Cellmentioning
confidence: 99%
“…To obtain maximum power output which the propeller delivers, efficiencies must be taken into account as given in Eq. 1 [18].…”
Section: Power and Mass Estimation Of Unmanned Aircraft System-based Pem Fuel Cellmentioning
confidence: 99%
“…During the launching, this percentage of throttle will vary with the wind conditions but it can be considered as standard in most of the duration of the launching. The percentage of throttle in the majority of the launchings is stablished at 70% [85][86][87] The percentage of throttle needed during cruise in the original ALO will be affected by weather conditions and flight altitude, but it can be considered as standard in the major part of the typical flights. The value of throttle in the majority of cruise situations was established at 15%:…”
Section: Flight Load Profilementioning
confidence: 99%
“…During the launching, this percentage of throttle will vary with the wind conditions but it can be considered as standard in most of the duration of the launching. The percentage of throttle in the majority of the launchings is stablished at 70% [85][86][87] Thus, it can be confirmed that the values of 4 and 1 kW, which were used during testing a typical flight load profile, are more demanding than during a normal flight.…”
Section: Battery Pack Testsmentioning
confidence: 99%
“…UAS system components are subjects of numerous researches and tests described in wide bibliography, available in electronic or paper forms; exemplary items [4][5][6][7][8][9][10] are worth citing. In the presented project challenges, one can distinguish certain trends of activities determining the success of the finally developed system.…”
Section: Nomentioning
confidence: 99%